Influence of TAS photoinitiator on UV-curing and performance of coating based on a bicycloaliphatic diepoxide and epoxy resin modified by black seed oil - Le, Xuan Hien; Do, Minh Thanh; Nguyen, Minh Duc (JST: Engineering And Technology For Sustainable Development, 2022)
Influence of photoinitiator triarylsulfonium hexafluoroantimonate salts (TAS) on UV-curing and performance of coatings based on 3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexane carboxylate – a bicycloaliphatic diepoxide (BCDE) and epoxy resin modified by black seed oil (EBSO) have been studied. The variation of TAS and functional groups of investigated coatings during UV-exposure was followed by infrared spectrometric analysis. The properties of UV-cured coatings such as gel fraction, relative hardness, flexibility and gloss were determined. It was shown that UV-curing of investigated coatings was markedly affected by their TAS initial concentration: When TAS initial concentration in the coatings enhanced from 6×10⁻³ mole/kg to 37.5×10⁻³ mole/kg, the photolysis of TAS, consumption of epoxy groups, formation of hydroxyl and ether groups increased from 3.78×10⁻³ mole/kg, 3.47 mole/kg, 40% , 177% to 28.5×10⁻³ mole/kg, 4.4 mole/kg, 327% and 1223%, respectively, after 1.2 s of UV-exposure; At the same time the performance of the UV-cured coatings was insignificantly changed: Their gel fraction and relative hardness decreased from 84.2% and 0.86 to 69.98% and 0.78 while flexibility and gloss at 60° remained unchanged to be 10 mm and 100%.